REINTERPRETATION OF THE MEANING OF KHALIFAH TOWARDS A NEW ISLAMIC CIVILIZATION: A CONTEXTUAL THEMATIC STUDY OF THE KHILAFAH VERSE - Mutamakin; Moch. Al-farizi; Ulil Albab, Muhamad Nizar (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2024)
The word khalifah is a central concept and a fundamental topic in human creation. Understanding this term is crucial to comprehending the essence and role of humanity in contemporary civilization. The aim of this research is to describe the essence of the word caliph, the nature of human civilization, and the reinterpretation of the meaning of caliph towards a new Islamic civilization. The researchers employed a thematic and contextual study of the Khilafah verses. Data collection was carried out through a study of several sources, namely the Al-Qur'an and Al-Hadith as well as several sources from books, articles, websites, etc. Researchers carry out in-depth data analysis and focus on the research objectives so that they can draw conclusions. The results of the research show firstly, the essence of the word caliph is a continuous process starting from fil ardlhi caliph to becoming caliph fil ardlhi. Second, the essence of human civilization is the change and continuity of the caliphate which is sunnatullah. Third, reinterpreting the meaning of khalifah towards a new Islamic civilization can be achieved by emphasizing concepts such as bismillahirrahmanirrahim and alhamdulillahi rabbil alamin. Keywords: Khalifah; Civilization; Reinterpretation; Islam. Abstrak Kata khalifah merupakan konsep sentral dan topik mendasar dalam penciptaan manusia. Memahami istilah ini sangat penting untuk memahami hakikat dan peran manusia dalam peradaban kontemporer. Tujuan penelitian ini adalah untuk mendeskripsikan hakikat kata khalifah, hakikat peradaban manusia, dan reinterpretasi makna khalifah menuju peradaban Islam baru. Peneliti menggunakan kajian tematik dan kontekstual terhadap ayat-ayat khilafah. Pengumpulan data dilakukan melalui kajian terhadap beberapa sumber, yaitu Al-Qur'an dan Al-Hadits serta beberapa sumber dari buku, artikel, situs web, dan lain-lain. Peneliti melakukan analisis data secara mendalam dan berfokus pada tujuan penelitian sehingga dapat menarik simpulan. Hasil penelitian menunjukkan pertama, hakikat kata khalifah merupakan proses yang berkesinambungan mulai dari khalifah fil ardlhi hingga menjadi khalifah fil ardlhi. Kedua, hakikat peradaban manusia adalah perubahan dan keberlanjutan kekhalifahan yang merupakan sunnatullah. Ketiga, reinterpretasi makna khalifah menuju peradaban Islam baru dapat dicapai dengan menekankan konsep-konsep seperti bismillahirrahmanirrahim dan alhamdulillahi rabbil alamin. Kata kunci: Khalifah; Peradaban; reinterpretasi; Islam.